Analisis Metode Pembelajaran IPA Di Kelas IV Pada MI Darul Huda - Rohmat Sauri; Dina Khairunnisa (STKIP Paris Barantai, 2023)
This research aims to find out what are the learning models at the SD / MI level, these learning models are intended to be seen as more prominent and relevant to the goals and demands of the needs in the world of education for this time. With the aim of the method, students can more easily understand the learning conveyed by the teacher, and this can increase the attractiveness of students when learning. It is known that teaching methods are an integral part of the application of teaching methods, strategies, techniques, and dance. Therefore, teachers must be able to master various learning methods that are adjusted to the characteristics and learning styles of students. This research uses qualitative methods with descriptive studies, analysis/observation studies and literature review methods or literature reviews by collecting data from several sources in the form of books and journals. By using the Google Scholar website. The data that has been collected is then managed to produce a literature review conclusion. In science learning, students still have difficulty understanding the material provided by the teacher using the discussion method because students are less capable and less active in learning with this method.Keywords: learning methods, teachers, students